Synthesis and antitubercular activity of new 1,3,4-oxadiazoles bearing pyridyl and thiazolyl scaffolds - Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Bhosle, Manisha R.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Mane, Ramrao A. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of more potent and safe new antitubercular agents, here new 2-pyridinyl substituted thiazolyl-5-aryl-1,3,4-oxadiazoles (6a-o), have been designed and synthesized using thionicotinamide as a starting, following novel multistep synthetic route. An intermediate, pyridinyl substituted thiazolyl acid hydrazide (4) when condensed with benzoic acids/nicotinic acids (5a-o) in the presence of silica supported POCl3 yielded better to excellent yields of the title compounds. All the synthesized compounds (6a-o) and intermediate acid hydrazide (4) have been screened for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG. Amongst them, 6f, 6j, 6l and 6o have revealed promising activity against M. bovis BCG at concentrations less than 3 mu g/mL. These compounds have shown low cytotoxicity (CC50: > 100 mu g/mL) towards four human cancer cell lines. Molecular docking study has also been performed against mycobacterial enoyl reductase (InhA) enzyme to gain an insight into the binding modes of these molecules and recorded good binding affinity. The ADME properties the title products have also been analyzed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: 1; 3; 4-Oxadiazole; Antitubercular activity; Cytotoxicity; Molecular docking; Pyridine; Thiazole

New bithiazolyl hydrazones: novel synthesis, characterization and antitubercular evaluation - Bhalerao, Mahendra B.; Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman; Mane, Ramrao A. (Bioorganic & Medicinal Chemistry Letters, 2017)
New bithiazolyl hydrazones (6a–l) have been first time synthesized by carrying novel one pot cyclocondensation of 5-acyl thiazoles (1a–b), thiosemicarbazide (2) and substituted phenacyl chlorides (4a–f) in freshly prepared ionic liquid, diisopropyl ethyl ammonium acetate (DIPEAc) at room temperature. The newly synthesized compounds have been evaluated for their antitubercular activity and the compounds 3b, 6a, 6b, 6d, 6e, 6f, 6g, and 6l have displayed noticeable antitubercular activity compared to Rifampicin with tolerable cytotoxicity. All these compounds were also screened for their antibacterial activity and found that, compounds 6j and 6k have exhibited a very good antibacterial activity. Molecular docking study has shown better harmony with the evaluation trend shown by these compounds under in vitro antitubercular screening.

Synthesis and antitubercular activity of new thiazolidinones with pyrazinyl and thiazolyl scaffolds - Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Khillare, Lalit D.; Arkile, Manisha A.; Sarkar, Dhiman; Mane, Ramrao A. (Journal of Heterocyclic Chemistry, 2017)
Emergence of multidrug resistant and extensively drug resistant tuberculosis has prompted to develop new molecular entities to treat the disease. A series of new 4-thiazolidinones with pyrazinyl and thiazolyl scaffolds has been synthesized, and their antitubercular activity is reported. The title 4-thiazolidinones, N-(pyrazinyl substituted thiazoloylamino)-2-aryl-4-thiazolidinones () have been first time prepared using pyrazinamide as a starting material via five successive steps. The purity and the structures of the intermediates (carboethoxythiazole, acid hydrazide, and azomethines) and title thiazolidinones () have been confirmed by TLC and spectral analyses, respectively. An antitubercular screening of the new 4-thiazolidinones has been performed on bacterial strains, Mycobacterium tuberculosis H37Ra and Mycobacterium BCG using the solutions of different concentrations of the compounds () and the screening results are presented. Compound has displayed notable antitubercular activity.